Effect of nitrogen fertilization on corn cultivation in La Carlota, Balzar canton, Ecuador - Cevallos, Klever; Zambrano, Leontes; Navarrete , Dioselina; Cisneros , Juana; Chila , Marcos; Burgos, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Corn (Zea mays L.) is produced in various countries, constituting a source of income for many families; for Ecuador, it represents an item with social and economic benefits. The objective of this research was to evaluate nitrogen fertilization in corn cultivation in La Carlota, Balzar canton, Ecuador. A randomized block experimental design was used with four treatments nitrogen fertilization (200, 300, 400 kg.ha-1) and control, (no application) and five replications. The variables evaluated were stem diameter, plant height, ear diameter, ear length, ear weight and yield per hectare. The results reflected that significant differences were observed (p<0.05) of 200 kg.ha-1 with respect to the other treatments. Therefore, it is important not to apply lower amounts or exceed the amount of N required per plant in each corn production unit.